Bivariate Survival Copula Analysis of Cataract Patients During Blindness: Cataract Cases at Undaan Eye Hospital, Surabaya - Jerry Dwi Trijoyo Purnomo; Purhadi Purhadi; Shofi Andari; Wahyu Dwi Rahmawati; Sri Harini (Pandawa Institute, 2026)
About 51% of all occurrences of blindness worldwide are caused by cataracts, which are the most common cause of blindness. According to the Rapid Assessment of Avoidable Blindness (RAAB) survey conducted in Indonesia between 2014 and 2016, East Java had the highest rate of blindness (4.4%), with cataracts accounting for 81.1% of cases. Approximately 10,000 cataract cases were reported at the Undaan Eye Hospital in Surabaya, one of the major eye hospitals in East Java, in 2023. This study aims to analyze the recovery time of patients undergoing cataract surgery on both eyes, considering the influencing factors. Data from bilateral cataract patients at the Undaan Eye Hospital in Surabaya between January 2023 and December 2024 were utilized. Gender, age, history of hypertension, heart disease, diabetes, gastric illness, stroke and cholesterol were among the characteristics that were examined. To determine the relationship between the recovery durations of both eyes following surgery, a bivariate survival analysis with Clayton and Gumbel copula functions was used for the analysis. The Gumbel copula was determined to be the better model for describing the recovery of bilateral cataract patients, with a QIC value of 1529.078 and a Kendall's Tau of 0.6636, indicating a moderate and positive dependency between the recovery periods of the right and left eye. The model estimate results showed a substantial correlation between recovery time and a few covariates, including age (hazard ratio of 0.516), history of hypertension (hazard ratio of 0.357), and history of diabetes (hazard ratio of 0.615). Compared to younger individuals, older patients recover more slowly. Furthermore, people with a history of diabetes and hypertension typically recover at a lower rate than those without these conditions.